2018
DOI: 10.1016/j.avsg.2018.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Abdominal Aorta During the Cardiac Cycle with the Sac-Anchoring Nellix Device

Abstract: The Nellix device uses polymer-filled endobags to stabilize the abdominal aortic aneurysm (AAA) sac which is described as endovascular aneurysm sealing (EVAS). We analyzed cardiac-gated computed tomography angiography scans of repaired AAA with EVAS in 4 patients to evaluate the geometry and cardiac pulsatility-induced deformation. Graft translation and aortic curvature changes were found to be minimal during the cardiac cycle. The mean ± standard deviation changes in renal-aorta angles (1.0 ± 0.9°) were less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This finding is in contrast with conventional transrenal or infrarenal endografts that do not seem to alter renal artery motion. 18 The renal branch angle change owing to pulsatile motion reported in the case series by Itoga et al 20 was similar to the Nellix-to-chimney angle change reported in the present study, indicating that the mechanical damping of renal artery movement is similar with EVAS and chEVAS, whereas a damping of SMA movement was observed with chEVAS only. In chE-VAS, this damping effect could contribute to a more stable configuration and therewith lead to less stent migration.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is in contrast with conventional transrenal or infrarenal endografts that do not seem to alter renal artery motion. 18 The renal branch angle change owing to pulsatile motion reported in the case series by Itoga et al 20 was similar to the Nellix-to-chimney angle change reported in the present study, indicating that the mechanical damping of renal artery movement is similar with EVAS and chEVAS, whereas a damping of SMA movement was observed with chEVAS only. In chE-VAS, this damping effect could contribute to a more stable configuration and therewith lead to less stent migration.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, albeit still small, we observed fairly greater magnitudes of motion (#1.7 mm). This finding might be explained by the transrenal positioning of the stents and thus the greater proximity of the stents to the heart compared to the infrarenal fixated stents in the study by Itoga et al 20 Interestingly, because the Nellix stents were fixated infrarenally, this study further found a mechanical damping effect of the Nellix device on renal artery movement. This finding is in contrast with conventional transrenal or infrarenal endografts that do not seem to alter renal artery motion.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…9,10 Because of the relative infrequency of cardiac-gated 3-dimensional (3D) imaging of the abdomen and the relatively recent arrival of EVAS, very little is known about the cardiac pulsatility-induced deformation of the abdominal aorta and its branches after EVAS. 11 Even less is known about how EVAS alters renal artery geometry and motion, which has been shown to be affected by EVAR. 12 In vivo motion, whether from cardiac pulsatility or respiration sources, could have potential relevance to aortic stent-graft design, branch vessel device design, therapeutic strategy, surveillance regimens, and failure mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Although curvature is a relatively novel parameter for aorto-iliac geometry quantification, curvature has been investigated as a predictor for complications after EVAR before. 18,19,[27][28][29][30][31] However, to fully describe the geometrics of a 3D CLL, torsion should be considered as well. Torsion describes the extent to which the induced curvature involves the third dimension.…”
Section: Discussionmentioning
confidence: 99%